Answer:
30 I N
Step-by-step explanation:
Answer:
![\displaystyle a_{n} = (2)^{2n -1} - (3) ^{n-1 }](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%20a_%7Bn%7D%20%20%3D%20%20%20%20%20%282%29%5E%7B2n%20-1%7D%20%20%20-%20%20%20%283%29%20%5E%7Bn-1%20%7D)
Step-by-step explanation:
we want to figure out the general term of the following recurrence relation
![\displaystyle \rm a_{n + 2} - 7a_{n + 1} + 12a_n = 0 \: \: where : \: \:a_1 = 1 \: ,a_2 = 5,](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%5Crm%20a_%7Bn%20%2B%202%7D%20-%207a_%7Bn%20%2B%201%7D%20%2B%2012a_n%20%3D%200%20%20%5C%3A%20%20%5C%3A%20where%20%3A%20%20%5C%3A%20%20%5C%3Aa_1%20%3D%201%20%5C%3A%20%2Ca_2%20%3D%205%2C%20)
we are given a linear homogeneous recurrence relation which degree is 2. In order to find the general term ,we need to make it a characteristic equation i.e
the steps for solving a linear homogeneous recurrence relation are as follows:
- Create the characteristic equation by moving every term to the left-hand side, set equal to zero.
- Solve the polynomial by factoring or the quadratic formula.
- Determine the form for each solution: distinct roots, repeated roots, or complex roots.
- Use initial conditions to find coefficients using systems of equations or matrices.
Step-1:Create the characteristic equation
![{x}^{2} - 7x+ 12= 0](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20-%207x%2B%2012%3D%200)
Step-2:Solve the polynomial by factoring
factor the quadratic:
![( {x}^{} - 4)(x - 3) = 0](https://tex.z-dn.net/?f=%28%20%7Bx%7D%5E%7B%7D%20%20-%204%29%28x%20-%203%29%20%3D%20%200)
solve for x:
![x = \rm 4 \:and \: 3](https://tex.z-dn.net/?f=x%20%3D%20%20%5Crm%204%20%5C%3Aand%20%5C%3A%203)
Step-3:Determine the form for each solution
since we've two distinct roots,we'd utilize the following formula:
![\displaystyle a_{n} = c_{1} {x} _{1} ^{n } + c_{2} {x} _{2} ^{n }](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20a_%7Bn%7D%20%20%3D%20c_%7B1%7D%20%20%7Bx%7D%20_%7B1%7D%20%5E%7Bn%20%7D%20%20%2B%20c_%7B2%7D%20%20%7Bx%7D%20_%7B2%7D%20%5E%7Bn%20%7D%20)
so substitute the roots we got:
![\displaystyle a_{n} = c_{1} (4)^{n } + c_{2} (3) ^{n }](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20a_%7Bn%7D%20%20%3D%20c_%7B1%7D%20%20%284%29%5E%7Bn%20%7D%20%20%2B%20c_%7B2%7D%20%20%283%29%20%5E%7Bn%20%7D%20)
Step-4:Use initial conditions to find coefficients using systems of equations
create the system of equation:
![\begin{cases}\displaystyle 4c_{1} +3 c_{2} = 1 \\ 16c_{1} + 9c_{2} = 5\end{cases}](https://tex.z-dn.net/?f=%20%20%5Cbegin%7Bcases%7D%5Cdisplaystyle%204c_%7B1%7D%20%20%20%20%2B3%20c_%7B2%7D%20%20%20%20%3D%201%20%20%5C%5C%2016c_%7B1%7D%20%20%20%20%2B%209c_%7B2%7D%20%20%20%20%20%3D%20%205%5Cend%7Bcases%7D)
solve the system of equation which yields:
![\displaystyle c_{1} = \frac{1}{2} \\ c_{2} = - \frac{1}{3}](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20c_%7B1%7D%20%20%3D%20%20%5Cfrac%7B1%7D%7B2%7D%20%20%20%20%20%5C%5C%20%20c_%7B2%7D%20%20%20%3D%20%20%20-%20%5Cfrac%7B1%7D%7B3%7D%20)
finally substitute:
![\displaystyle a_{n} = \frac{1}{2} (4)^{n } - \frac{1}{3} (3) ^{n }](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%20a_%7Bn%7D%20%20%3D%20%20%5Cfrac%7B1%7D%7B2%7D%20%20%20%284%29%5E%7Bn%20%7D%20%20%20-%20%20%5Cfrac%7B1%7D%7B3%7D%20%20%283%29%20%5E%7Bn%20%7D)
![\displaystyle \boxed{ a_{n} = (2)^{2n-1 } - (3) ^{n -1}}](https://tex.z-dn.net/?f=%20%5Cdisplaystyle%20%5Cboxed%7B%20a_%7Bn%7D%20%20%3D%20%20%20%20%282%29%5E%7B2n-1%20%7D%20%20%20-%20%20%20%283%29%20%5E%7Bn%20-1%7D%7D)
and we're done!
The correct answer is c because when I graphed each one the only one that passed through your given coordinate was that equation
16 girls. 12 divided by 4 is 3, so this means that you have to take 4 and multiply it by 4 which equals to 16.
A postcard is in the shape of a parallelogram. A parallelogram is a quadrilateral with two pair of parallel sides, opposite sides and opposite angles are equal.
Since, the postcard has an area of 12 square inches.
Since, area of parallelogram = ![base \times height](https://tex.z-dn.net/?f=base%20%5Ctimes%20height)
As area of parallelogram is 12, it means that the product of base and height is 12 square inches.
So, the possible dimensions of postcard are 3 inches and 4 inches and 2 inches and 6 inches.
So, base = 3 inches , height = 4 inches or base = 4 inches , height = 3 inches.
So, base = 2 inches, height = 6 inches or base = 6 inches , height = 2 inches.